WORKSHOP TARI KHAS PAMEKASAN SEBAGAI PENGUATAN SUMBER BELAJAR LOCAL WISDOM DI SEKOLAH DASAR - Perdana, Parrisca Indra; Harsiwi, Nova Estu; Rachma, Evi Pebri Ila (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2023)
The low level of knowledge and skills of teachers regarding Pamekasan music and dance arts can have an impact on the lack of implementation of local culture in learning at school. In fact, the use of local Madurese culture in art learning can reconstruct a unique Madurese identity. Therefore, there is a need for training and assistance in traditional arts culture for teachers to have knowledge and skills of local Madurese culture in the traditional arts of music and dance. This training and mentoring activity is carried out in 3 steps, namely ToT (Training of Trainer) activities, Workshop Activities and Mentoring Activities. ToT activities produce qualified trainers to accompany teachers and students in learning dance and music material. Workshop activities can improve soft skills and cultural literacy for teachers regarding the implementation of Madurese traditional arts (music and dance) in elementary schools. Mentoring activities can strengthen teacher skills and introduce Madurese traditional arts to students.